Penatalaksanaan Fisioterapi Pada Terapi Latihan Pada Post Op Sectio Caesarea Di Rsud Dr. Moewardi Surakarta - Sari, Lisa Fibriyani Wulan, Umi Budi Rahayu, S.Fis, S.Pd, M.Kes (2015)
Background: section caesaria is a way childbirth embrio with slice at uterus wall by front wall of stomacth. sectiocaesaria with indication disproportion head pelvis (DKP), embryo emergency, anomali location, malpresentation embryo, SC history before suspicious reptureutery is treatening, preeklamsia and hypertensy, old partus. Physiotherapy party has problem may be causes SC operating like: painful in slice area because torn tissue in wall stomach and uterus. The other problem is muscle of stomach decrase potential because slice in wall stomach, deep vein thrombosis (DVT) caused thickness of blood increases because hemoconsentrationmechanism happen of mother pasca operation SC. Method: One of modality physiotherapy is exercise where implementation uses movement tranning of body pasive and active. Purpose: To know benefit giving therapy with modality therapy exercise to defense and strength elasticity muscle wall stomach, base musle of hip, ligament and tissues and fasia, treatment and maintenance body esthetic. Result: After intervention 6 times therapy result painful reduces, muscle stomach increase and increasing ability functional of patient. Conclusion: exercise therapy reduces painful, increasing strength muscle stomach and ability functional of patient.